Simulation modeling for heart attack patient by mapping cholesterol level - Jossy P George; Suhas M Gaikwad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Cholesterol is a complex structural material made up of four-fused hydrocarbon rings. There is a hydrocarbon tail linked at one end of the structure, while the hydroxyl group linked to each other on the other end. To one end of the structure, a hydrocarbon tail linked and to the other end, a hydroxyl group linked to each other. High cholesterol level is one among the major risk factors of a heart attack. It is feasible to compute and control the cholesterol level of a cardiovascular patient by making use of intended Mathematical modeling in System Dynamics (S.D.). Moreover, by simulating proposed set of equations for a heart attack patient, recovery accomplished at a faster pace. Because of S.D., a substantial amount of reduction in the patient's Cardiovascular Disease achieved by control over the sterol level of the heart patient. This simulation modeling is an attempt made in translational research domain and is useful in the healthcare industry health care industry. It will minimize the risk of heart stroke and maintain a healthy life.